Experimental Design of Lip Moisturizer as a Patchouli-Based Innovation Product - Friesca Erwan; Syaifullah Muhammad; Raihan Dara Lufika; Eva Oktaviana; Nadiatul Azizah; Elza Badriati Miftah; Fathan Mubin; Luthfiah Zahra Larosa; Siti Hajar (Universitas Syiah Kuala, 2022)
Patchouli oil, a type of essential oil, is one of Indonesian’s non-oil and gas export commodities accounted for one of the sources of Indonesian foreign exchange. Patchouli alcohol is commonly used in the cosmetic and perfume industries as well as the fragrance ingredient in the household products, one of which is used in lip moisturizer product. Lip moisturizer is a cosmetic product that was created with the similar essence of lipstick saves for its colorless in nature hence the translucent appearance. As a moisturizer, lip moisturizer can be used to moisturize the lips to avoid dry and chapped lips. Producing lip moisturizer involves four steps of formulation, which are mixing the solid components, mixing the liquid components, mixing of both the solid and liquid components, and adding the active substances and the patchouli oil. The study conducted two times of experiment, and it can be concluded that the second experiment can be used for lip skin. The execution of the test was based on the stability and homogeneity tests that meet the terms and conditions that have been set.